Pengaruh Substitusi Daging Ayam Broiler Dengan Jamur Salju (Tremella Fuciformis) Pada Kualitas Nugget Ayam - Eva Yuniarti Utami; Djalal Rosyidi; Eny Sri Widyastuti (Faculty of Animal Science Universitas Brawijaya, 2015)
The research was purposed find out the effect of substitution broiler meat with white jelly mushroom (Tremella fuciformis) on qualities and organoleptic of chicken nugget. The result were expected to be used as an information about the effect of substitution broiler meat with white jelly mushroom on the qualities and organoleptic of chicken nuggets and these informations can also be used for further research. The material of the research were chicken nuggets with different level substitution of mushroom. Design used in this research was Completely Randomized Design (CDR) with three replication. The treatments were the concentration of the white jelly mushroom substitution, i.e: without substitution (P0), 15% (P1), 30% (P2) and 45% (P3). The parameter measured were texture, microstructure, WHC, pH, organoletic, water, lipid and protein content. Data were analyzed by analysis.of variance and if there were significantly different means among treatments it was then followed by Duncanâ€™s multiple Range Test. The result of research showed that chicken nugget with different level substitution mushroom was high significant different effect (P<0.01) on moisture, and significant different on protein content. The average moisture content of chicken nugget of (P0), (P1), (P2) and (P3) was; 67.05%, 67.33%, 69.29% and 69.36% respectively, protein content 30.85%, 30.77%, 26.26% and 20.99%, but not significant effect (P>0.05) of texture, WHC, pH, lipid content and organoleptic. The average textureÂ of (P0), (P1), (P2) and (P3) was; 11.76 N, 14.4 N, 14.22 N and 17.38 N respectively. The WHC 55.83 %, 58.7 %, 63.58 % and 65.08%. pH 6.53, 6.41, 6.32 and 6.25 and lipid content 1.16%, 1.23%, 1% and 1.14%. the treatments also gave a different discription on microstructure.